Unintentional Role Models: Links Between Maternal Eating Psychopathology and the Modelling of Eating Behaviours. (25th January 2013) - Palfreyman, Zoe; Haycraft, Emma; Meyer, Caroline
Abstract This study explored the relationships between maternal modelling of eating behaviours with reported symptoms of maternal eating psychopathology, anxiety and depression. Mothers (N = 264) with a child aged 1.5 to 8 years completed three self‐report measures designed to assess modelling of eating behaviours, eating psychopathology and levels of anxiety and depression. The study found that higher levels of maternal eating psychopathology were positively associated with eating behaviours that were unintentionally modelled by mothers but that maternal eating psychopathology was not associated with more overt/intentional forms of parental modelling. In addition, higher levels of maternal depression were associated with lower levels of both unintentional and intentional forms of maternal modelling, whereas maternal anxiety was not found to correlate with modelling behaviours. This study highlights the possible detrimental influences of maternal mental health in relation to mothers providing their child with a positive parental role model around eating and feeding. Copyright © 2013 John Wiley & Sons, Ltd and Eating Disorders Association.